Perbandingan Kerangka Hukum untuk Perselingkuhan Non-Fisik di Indonesia dan Brunei Darussalam - Diah Nuraini; Nur Mifchan Solichin; Nasih Burhani (Institut Agama Islam Negeri (IAIN) Kediri, 2025)
The phenomenon of emotional infidelity or emotional affair has increasingly gained attention due to its serious impact on marital harmony, even though it does not involve physical relations. This topic was chosen because, in practice, non-physical infidelity often leads to conflict, even divorce, yet its regulation in family law in both Indonesia and Brunei Darussalam remains unclear. This study aims to examine and compare how the two countries address the issue of emotional infidelity within their respective legal frameworks. This research is a normative legal study employing a comparative approach. Data were collected through library research and analysis of legal documents, including statutes, regulations, and court decisions in Indonesia and Brunei Darussalam, and then analyzed using the theory of legal pluralism and Zweigert and Kötz’s comparative law methodology. The findings reveal that Indonesia does not yet have specific provisions that explicitly categorize emotional infidelity as a legal violation, although it is often cited as grounds for divorce in religious courts. In contrast, Brunei Darussalam has stricter regulations through the Islamic Family Law Order 1999 and the Syariah Penal Code Order 2013, which classify emotional infidelity as part of moral and religious violations with clearer legal consequences. These findings are significant as they highlight a regulatory gap that affects the protection of marital institutions in Indonesia. By understanding this comparison, the study is expected to contribute to the development of Islamic family law in Indonesia, particularly in formulating more responsive regulations toward the increasingly complex phenomenon of non-physical infidelity in the digital era.